ZTF J1901+5309: a 40.6-min orbital period eclipsing double white dwarf system. (30th March 2020) - Coughlin, Michael W; Burdge, Kevin; Sterl Phinney, E; van Roestel, Jan; Bellm, Eric C; Dekany, Richard G; Delacroix, Alexandre; Duev, Dmitry A; Feeney, Michael; Graham, Matthew J; Kulkarni, S R; Kupfer, Thomas; et al.
ABSTRACT: The Zwicky Transient Facility has begun to discover binary systems with orbital periods that are less than 1 h. Combined with dedicated follow-up systems, which allow for high-cadence photometry of these sources, systematic confirmation and characterization of these sources are now possible. Here, we report the discovery of ZTF J190125.42+530929.5, a 40.6-min orbital period, eclipsing double white dwarf binary. Both photometric modelling and spectroscopic modelling confirm its nature, yielding an estimated inclination of i = 86.2^+0.6_-0.2 deg and primary and secondary effective temperatures of T_eff = 28 000^+500_-500 and 17 600^+400_-400 K, respectively. This system adds to a growing list of sources for future gravitational-wave detectors and contributes to the demographic analysis of double degenerates.